2009
DOI: 10.1111/j.1600-0897.2009.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Antiphospholipid Antibodies Induce a Pro‐Inflammatory Response in First Trimester Trophoblast Via the TLR4/MyD88 Pathway

Abstract: Problem-Women with antiphospholipid antibodies (aPL) are at risk for recurrent miscarriage, preeclampsia and preterm labor. aPL target the placenta directly by binding to Beta 2 -Glycoprotein I (β 2 GPI) expressed on the surface of trophoblast cells. The objective of this study was to determine the effects of aPL on trophoblast function and the mechanisms involved.Method of study-First trimester trophoblast were treated with anti-β 2 GPI monoclonal antibodies and patient-derived aPL, after which cell survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
224
3
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 172 publications
(246 citation statements)
references
References 57 publications
8
224
3
4
Order By: Relevance
“…Both clinical and experimental observations suggest that pregnancy loss in these patients may involve an inflammatory response at the maternal-fetal interface, as well as disruption of normal trophoblast survival and function (Sebire et al, 2002;Bose et al, 2006;Redecha et al, 2007Redecha et al, , 2008. Mulla et al (2009) demonstrated for the first time that anti-b2GPI antibodies elicit a dose-dependent response in human first trimester trophoblast cells. They showed that antib2GPI antibodies at lower concentrations markedly triggered an inflammatory response in HTR8 trophoblast cells, characterized by increased secretion of IL8, MCP1, GROa and IL1B in a TLR4/MyD88-dependent manner, whereas at high concentrations, these antibodies induced cell death and apoptosis.…”
Section: Trophoblastsmentioning
confidence: 99%
See 4 more Smart Citations
“…Both clinical and experimental observations suggest that pregnancy loss in these patients may involve an inflammatory response at the maternal-fetal interface, as well as disruption of normal trophoblast survival and function (Sebire et al, 2002;Bose et al, 2006;Redecha et al, 2007Redecha et al, , 2008. Mulla et al (2009) demonstrated for the first time that anti-b2GPI antibodies elicit a dose-dependent response in human first trimester trophoblast cells. They showed that antib2GPI antibodies at lower concentrations markedly triggered an inflammatory response in HTR8 trophoblast cells, characterized by increased secretion of IL8, MCP1, GROa and IL1B in a TLR4/MyD88-dependent manner, whereas at high concentrations, these antibodies induced cell death and apoptosis.…”
Section: Trophoblastsmentioning
confidence: 99%
“…Recently, attention has been paid to different cell types, such as trophoblasts. Mulla et al (2009) demonstrated that aPL triggers a placental inflammatory response via the TLR4⁄MyD88 pathway and indicated the potential value of studies in these cells. Besides thrombosis and fetal loss, the clinical spectrum of APS is becoming more complex as additional clinical manifestations are attributed to the syndrome.…”
Section: Open Questionsmentioning
confidence: 99%
See 3 more Smart Citations